1995
DOI: 10.1084/jem.181.2.669
|View full text |Cite
|
Sign up to set email alerts
|

Sequential contribution of L- and P-selectin to leukocyte rolling in vivo.

Abstract: Leukocyte recruitment into inflammatory sites is initiated by a reversible transient adhesive contact with the endothelium called leukocyte rolling, which is thought to be mediated by the selectin family of adhesion molecules. Selectin-mediated rolling precedes inflammatory cell emigration, which is significantly impaired in both P- and L-selectin gene-deficient mice. We report here that approximately 13% of all leukocytes passing venules of the cremaster muscle of wild- type mice roll along the endothelium at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
463
4
3

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 552 publications
(497 citation statements)
references
References 53 publications
27
463
4
3
Order By: Relevance
“…However, in vivo studies have demonstrated a role for P-and Lselectin but not E-selectin in mouse leucocyte rolling, during trauma and cytokine stimulation (Ley et al, 1995). Furthermore, tumours are known to produce cytokines such as interleukin 1 (IL-1) and TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…However, in vivo studies have demonstrated a role for P-and Lselectin but not E-selectin in mouse leucocyte rolling, during trauma and cytokine stimulation (Ley et al, 1995). Furthermore, tumours are known to produce cytokines such as interleukin 1 (IL-1) and TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the disorganized flow characteristics of the tumour enabling firm adhesion without initial rolling. The adhesion molecules P-selectin, E-selectin, L-selectin (CD62P and L) and VCAM-1 are all involved in regulating in vivo leucocyte rolling and adhesion (Ley et al, 1995). As rolling of effector cells was not observed in our studies, it is possible that there is down-regulation of adhesion molecules on the tumour endothelium, and this is currently being investigated in our model.…”
Section: Discussionmentioning
confidence: 82%
“…Capture efficiencies of non-deformable microbeads targeted with physiological capture ligands on purified selectin substrates are on the order of ∼ 10-35% [20,47] under similar conditions. Leukocytes roll on cytokine-stimulated endothelium with an efficiency of ∼20-30% in mouse venules [38], although the in vivo situation presents a substantially different target geometry and flow conditions. Although the wrinkled microbubbles described here achieved a degree of deformation similar to activated leukocytes [18,43], our results suggest that deformation alone does not necessarily compensate for inefficient binding biomechanics.…”
Section: Discussionmentioning
confidence: 99%
“…Trachea intubation to promote spontaneous respiration was accomplished with PE 90 tubing, and microbubbles were introduced into the right jugular vein through a PE 20 cannula. A cremaster muscle was exteriorized and continuously superfused with an isothermic bicarbonate-buffered solution as described [38]. The exteriorized cremaster was pinned to a custom-made microscope stage and placed beneath a saline immersion objective for intravital microscopy (Zeiss SW 40/0.8 NA).…”
Section: Intravital Microscopymentioning
confidence: 99%